Pernikahan Adat Pepadun Perspektif Pendidikan Islam - Zakia Al Erza, Rahma; Pahrudin, Agus; Anwar, Chairul (Kamaya: Jurnal Ilmu Agama, 2024)
This research explores the implementation of the marriage customs of the Lampung Pepadun community in the Sungkai Bunga Mayang clan from an Islamic education perspective. The research background reflects the complexity of Lampung traditional marriages, where traditional traditions and Islamic norms often blend. The traditional Lampung wedding ceremony in the Sungkai Bunga Mayang clan involves Rasan Sanak (elopement) and Rasan Tuho (parental consent). This research aims to analyze and describe the implementation of wedding customs, with a focus on compliance with the principles of Islamic education. The method used is descriptive qualitative research, describing the research object and analyzing it. This research is descriptive in nature which is analyzed qualitatively in order to describe or describe the condition of an object and then analyze it. This research was structured based on field research by collecting data through interviews, observation, documentation and from various literature related to this research study. The results of the research show that the Lampung Pepadun community in the Sungkai Bunga Mayang clan consistently maintains and maintains traditional traditions, such as intar payu, intar bright field, intar bright, intar manum, and sembambangan. This tradition is in line with Islamic education, providing teachings about attitudes and behavior in accordance with Islamic values. However, several marriage practices were found that were not fully in accordance with Islamic teachings, such as high dowries or exchange of goods that were not according to Islamic law. The conclusion of this research highlights the need to increase public awareness of the principles of Islamic education in carrying out traditional Lampung weddings. Efforts to integrate Islamic values ​​into wedding traditions can produce marriages that are more balanced and in accordance with religious teachings.